COMPOSIÇÃO GRAVIMÉTRICA DOS RESÍDUOS SÓLIDOS DOS ALUNOS DO CURSO DE ENGENHARIA AMBIENTAL E SANITÁRIA DA UEMS - DA SILVA, Vitoria Bitencourt,; KONRADT-MORAES, Leila Cristina,; BRAGA, Gabriel Bastos, (ANAIS DO ENIC, 2023)
-